Light emitting element
The ultraviolet light emitting device addresses the challenges of reduced luminous efficiency and reverse bias deterioration by employing a quantum well structure with specifically doped barrier layers, resulting in improved recombination efficiency and reliability.
Patent Information
- Application Number
- JP2023161494
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-04-07
AI Technical Summary
In ultraviolet light emitting devices using group III nitride semiconductors, the reduction in luminous efficiency due to QCSE (quantum confinement stark effect) and the deterioration of characteristics during reverse bias, such as increased leakage current and decreased breakdown voltage, pose significant challenges.
The light emitting device incorporates a quantum well structure with a first barrier layer doped with undoped or n-type impurities and a second barrier layer in contact with the well layer, doped with n-type impurities at a higher concentration than the first barrier layer, to improve light emitting recombination and reduce reverse bias deterioration.
This configuration enhances the probability of light emitting recombination while minimizing the deterioration of characteristics during reverse bias, thereby improving the overall efficiency and reliability of the ultraviolet light emitting device.
Smart Images

Figure 2025052670000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a light-emitting device. [Background technology]
[0002] The ultraviolet wavelength of solid-state light-emitting devices using III-nitride semiconductors corresponds to a wavelength band of approximately 210 to 400 nm. In particular, UVC (wavelength 100 to 280 nm) is known to be effective for sterilization and disinfection, and there is a growing demand for III-nitride semiconductor LEDs that emit ultraviolet light with an emission wavelength corresponding to UVC. Ultraviolet LEDs are configured by forming an AlN layer on a sapphire substrate, and then laminating an n-type layer, active layer, and p-type layer made of AlGaN on the AlN layer.
[0003] In LEDs using group III nitride semiconductors, distortion caused by the lattice mismatch between the well layer and the barrier layer in the active layer generates a piezoelectric field, which reduces the light emission efficiency due to the quantum confined Stark effect (QCSE). In UV LEDs, the Al composition of AlGaN is high, so the reduction in light emission efficiency due to QCSE becomes more pronounced.
[0004] Known methods for suppressing the decrease in luminous efficiency due to QCSE include making the well layer thinner and doping the barrier layer with Si. Patent Document 1 describes that doping the barrier layer with Si makes the slope of the well layer band (energy band in the direction perpendicular to the main surface of the substrate) closer to flat, thereby improving the light output of deep-ultraviolet LEDs. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2021-34732 Summary of the Invention [Problem to be solved by the invention]
[0006] On the active layer, a Mg-doped p-type layer such as an electron blocking layer is formed. In the method of Patent Document 1, the distance between the n-type and p-type is small because the barrier layer is doped with Si, which causes various deteriorations in characteristics when reverse biased. For example, this causes an increase in leakage current, a decrease in breakdown voltage, deterioration in ESD characteristics, deterioration in reliability, etc.
[0007] The present invention has been made in view of the above background, and aims to provide a light-emitting element in which deterioration of characteristics under reverse bias is reduced. [Means for solving the problem]
[0008] One aspect of the present invention is In an ultraviolet light-emitting device using a group III nitride semiconductor, an n-type layer made of a group III nitride semiconductor containing n-type Al; an active layer located on the n-type layer, the active layer being made of a group III nitride semiconductor containing Al and having a quantum well structure having a well layer and a barrier layer; a p-type layer located on the active layer and made of a group III nitride semiconductor containing p-type Al; having The barrier layer comprises: a first barrier layer which is undoped or doped with an n-type impurity; a second barrier layer located on the first barrier layer, in contact with the surface of the well layer facing the n-type layer, and doped with an n-type impurity at a higher concentration than the first barrier layer. Effect of the Invention
[0009] In the above embodiment, the barrier layer has a structure including a first barrier layer that is undoped or doped with n-type impurities, and a second barrier layer that is located on the first barrier layer, contacts the well layer, and is doped with n-type impurities at a higher concentration than the first barrier layer, thereby improving the radiative recombination probability and reducing the deterioration of characteristics under reverse bias. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view showing the configuration of a light-emitting device in embodiment 1, taken along a direction perpendicular to a main surface of a substrate. [Diagram 2] FIG. 2 is a cross-sectional view showing the configuration of an active layer, taken along a direction perpendicular to the main surface of the substrate. [Diagram 3] FIG. 13 is a diagram showing a band diagram and a thickness direction distribution of carrier concentration of a light-emitting element when 6 V is applied. [Figure 4] FIG. 13 is a diagram showing a band diagram and a thickness direction distribution of carrier concentration of a light-emitting element when 6 V is applied. [Diagram 5] FIG. 13 is a diagram showing a band diagram and a thickness direction distribution of carrier concentration of a light-emitting element when 6 V is applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The light-emitting element is an ultraviolet-emitting light-emitting element using a Group III nitride semiconductor and has an n-type layer made of an n-type Group III nitride semiconductor containing Al, an active layer located on the n-type layer, made of a Group III nitride semiconductor containing Al, and having a quantum well structure having a well layer and a barrier layer, and a p-type layer located on the active layer and made of a p-type Group III nitride semiconductor containing Al, the barrier layer having a first barrier layer that is undoped or doped with an n-type impurity, and a second barrier layer located on the first barrier layer, in contact with the surface of the well layer facing the n-type layer, and doped with an n-type impurity to a higher concentration than the first barrier layer.
[0012] In the light emitting device, the uppermost barrier layer, which is the layer closest to the p-type layer among the barrier layers, may be a non-doped Group III nitride semiconductor, which can further reduce deterioration of characteristics when reverse bias is applied.
[0013] In the light-emitting device, the first barrier layer is non-doped, and the second barrier layer has a Si concentration of 1×10 18 ~2×10 19 cm -3 The probability of radiative recombination can be further improved, and deterioration of characteristics under reverse bias can be further reduced.
[0014] In the above light-emitting device, the first barrier layer may have a thickness of 2 to 20 nm, and the second barrier layer may have a thickness of 2 to 20 nm, which can further improve the radiative recombination probability and further reduce deterioration of characteristics under reverse bias.
[0015] The light-emitting device may further include a hole blocking layer between the n-type layer and the active layer, the hole blocking layer being made of AlGaN or AlN having a higher Al composition than the barrier layer, and being in contact with the active layer. This can flatten the band of the entire active layer, thereby improving the efficiency of hole injection into the active layer.
[0016] The light-emitting device may further include a superlattice layer located between the n-type layer and the hole blocking layer in contact with the hole blocking layer, the superlattice layer being formed by alternately stacking III-nitride semiconductors having different Al compositions.
[0017] In the above light-emitting device, the active layer may have an MQW structure.
[0018] (Embodiment 1) Fig. 1 is a diagram showing the configuration of a light-emitting element 1 in embodiment 1, and is a cross section taken along a direction perpendicular to the main surface of a substrate. As shown in Fig. 1, the light-emitting element 1 in embodiment 1 includes a substrate 10, an n-type layer 11, a superlattice layer 12, a hole blocking layer 13, an active layer 14, an electron blocking layer 15, a compositionally graded layer 16, a p-type contact layer 17, an n-side electrode 18, and a p-side electrode 19.
[0019] 1. Light-emitting element configuration The configuration of each layer of the light-emitting device 1 in embodiment 1 will be described in detail.
[0020] The substrate 10 is a substrate made of sapphire with a c-plane as the principal surface. The plane orientation of the principal surface of the sapphire may be the a-plane. In addition, the substrate may have an off angle of 0.1 to 2 degrees in the m-axis direction. The back surface of the substrate 10 (the surface opposite to the n-type layer 11) serves as the main light extraction surface. An anti-reflection film may be provided on the back surface of the substrate 10 to improve the light extraction efficiency. In addition, the surface of the substrate 10 may be provided with irregularities to improve the light extraction efficiency. In addition, an AlN substrate or an AlN template substrate in which an AlN layer is formed on a sapphire substrate may be used as the substrate 10.
[0021] The thickness of the substrate 10 is, for example, 1000 μm or less, and preferably 400 μm or more and 700 μm or less, which can suppress light extraction from the side surface of the substrate 10 and improve the on-axis intensity.
[0022] The substrate 10 may be removed by a method such as LLO (laser lift-off), etc. An anti-reflection film may be provided on the back surface of the substrate 10 to improve light extraction efficiency.
[0023] The n-type layer 11 is located on the substrate 10. The n-type layer 11 is made of n-AlGaN. The Al composition (the molar ratio of Al in the whole group III metals) is, for example, 60 to 90%. The n-type impurity is Si, and the Si concentration is, for example, 1×10 18 ~5×10 19 cm -3 The thickness of the n-type layer 11 is, for example, 0.5 to 5 μm. The C concentration of the n-type layer 11 is 1×10 15 ~1×10 19 cm -3 The n-type layer 11 may be composed of a plurality of layers. Also, an underlayer made of AlN may be provided between the substrate 10 and the n-type layer 11. Also, an element other than Si may be used as the n-type impurity.
[0024] The superlattice layer 12 is located on the n-type layer 11. The superlattice layer 12 has a structure in which AlGaN layers having different Al compositions are alternately laminated. By providing the superlattice layer 12, the strain in the active layer 14 can be relaxed.
[0025] The superlattice layer 12 has a two-layer structure in which, for example, a barrier layer made of Si-doped AlGaN and a well layer made of non-doped AlGaN are laminated in this order from the n-type layer 11 side. The Al composition of the barrier layer of the superlattice layer 12 is in the same range as the Al composition of the barrier layer 140 of the active layer 14, and may be the same. The Al composition of the well layer of the superlattice layer 12 is in the same range as the Al composition of the well layer 141 of the active layer 14, and may be the same. The thickness of the barrier layer of the superlattice layer 12 is 2 to 20 nm, and the thickness of the well layer of the superlattice layer 12 is 0.5 to 10 nm.
[0026] The hole blocking layer 13 is located on and in contact with the superlattice layer 12. The hole blocking layer is made of AlGaN or AlN having a higher Al composition than the barrier layer 140 of the active layer 14. By providing the hole blocking layer 13 directly under the active layer 14, the band of the entire active layer 14 can be flattened. This increases the probability of radiative recombination in the well layer 141, thereby improving the light emission efficiency. In addition, it is possible to prevent holes injected from the p-side electrode 19 from diffusing beyond the active layer 14 to the n-type layer 11 side.
[0027] The thickness of the hole blocking layer 13 is preferably one molecular layer to 2 nm. Within this range, the hole blocking layer 13 can fully exhibit its function. In addition, electrons can be easily tunneled to the active layer 14, improving the efficiency of electron injection into the active layer 14. In the case of AlN, one molecular layer is approximately 0.26 nm.
[0028] When the hole blocking layer 13 is made of AlGaN, the Al composition is preferably 80% or more.
[0029] The hole blocking layer 13 does not need to be in contact with the active layer 14, and a layer may be provided between the hole blocking layer 13 and the active layer 14. However, in order to enhance the band flattening effect of the active layer 14, the distance between the hole blocking layer 13 and the active layer 14 is preferably 10 nm or less, and it is most preferable that the hole blocking layer 13 and the active layer 14 are in contact with each other.
[0030] The active layer 14 is located on the hole blocking layer 13. The active layer 14 has a quantum well structure (SQW) with one well layer, in which a barrier layer 140, a well layer 141, and a top barrier layer 142 are stacked in this order from the hole blocking layer 13 side. The top barrier layer is the layer of the barrier layers of the active layer 14 that is closest to the electron blocking layer 15 side.
[0031] The barrier layer 140 has a structure in which a first barrier layer 140A and a second barrier layer 140B are laminated in this order from the hole blocking layer 13 side. The first barrier layer 140A is located on and in contact with the hole blocking layer 13. The second barrier layer 140B is located on and in contact with the first barrier layer 140A, and is in contact with the surface of the well layer 141 on the n-type layer 11 side.
[0032] The first barrier layer 140A is made of AlGaN having a larger Al composition than the well layer 141, and the Al composition is, for example, 50 to 100%. The first barrier layer 140A is a non-doped layer. It may be a layer doped with Si at a low concentration, for example, with a Si concentration of 1×10 18 cm -3 More preferably, it is 1×10 17 cm -3 The following is more preferably non-doped. The thickness of the first barrier layer 140A is preferably 2 to 20 nm. If the Si concentration and thickness are within this range, the Si concentration in the entire barrier layer 140 can be reduced while the function as a carrier barrier is sufficiently ensured.
[0033] The second barrier layer 140B is made of AlGaN having a higher Al composition than the well layer 141, and the Al composition is, for example, 50 to 100%. The Al composition of the second barrier layer 140B may be the same as the Al composition of the first barrier layer 140A. The second barrier layer 140B is a layer doped with Si at a higher concentration than the first barrier layer 140A. The Si concentration of the second barrier layer 140B is, for example, 1×10 18 ~2×10 19 cm -3The second barrier layer 140B has a thickness of, for example, 2 to 20 nm. If the Si concentration and thickness are within this range, the band flattening effect of the active layer 14 can be sufficiently enhanced, and the Si concentration in the entire barrier layer 140 can be reduced.
[0034] The average Si concentration in the entire barrier layer 140 is 0.5×10 18 ~1×10 19 cm -3 It is preferable that the internal electric field between the p-type and n-type be reduced, and deterioration of characteristics during reverse bias can be reduced.
[0035] In the first embodiment, the Si concentration is changed in two steps, but it may be changed in three or more steps, or may be changed continuously. For example, a third barrier layer having an intermediate Si concentration between the first barrier layer 140A and the second barrier layer 140B may be provided between the first barrier layer 140A and the second barrier layer 140B.
[0036] As described above, in the light-emitting device 1 of the first embodiment, the barrier layer 140 has a two-layer structure of the non-doped first barrier layer 140A and the Si-doped second barrier layer 140B. This makes it possible to flatten the band of the active layer 14. As a result, it is possible to reduce QCSE and improve the radiative recombination probability.
[0037] In addition, since the first barrier layer 140A is non-doped, the Si concentration can be reduced compared to the case where the entire barrier layer 140 is doped with Si. Therefore, the internal electric field between the p-type and n-type can be reduced, and deterioration of characteristics when a reverse bias is applied to the light-emitting element 1 in the first embodiment can be reduced. For example, it is possible to reduce the leakage current when a reverse bias is applied, suppress a decrease in the breakdown voltage, suppress deterioration of ESD characteristics, and improve reliability.
[0038] The well layer 141 is made of AlGaN, and the Al composition is set according to the desired emission wavelength. The Si concentration of the well layer 141 is, for example, 1×10 18 cm -3The well layer 141 may be undoped. The well layer 141 has a thickness of, for example, 0.5 to 5 nm.
[0039] The top barrier layer 142 is the topmost layer (the layer closest to the p-type contact layer 17) of the barrier layers of the active layer 14, and is in contact with the electron block layer 15. The top barrier layer 142 is made of AlGaN having a higher Al composition than the well layer 141, and the Al composition is, for example, 50 to 100%. The Al composition of the top barrier layer 142 may be the same as the Al composition of the first barrier layer 140A and the second barrier layer 140B. The thickness of the top barrier layer 142 is preferably 0.5 to 10 nm. The top barrier layer 142 may be undoped or Si-doped, but is preferably undoped from the viewpoint of reducing deterioration of characteristics during reverse bias.
[0040] In the first embodiment, the active layer is an SQW, but may be an MQW having two or more well layers. In the case of an MQW structure, it is preferable that each of the barrier layers 140 other than the uppermost barrier layer 142, which is the uppermost layer among the barrier layers 140, has a two-layer structure of the first barrier layer 140A and the second barrier layer 140B as described above. In the case of an MQW structure, it is also preferable that the uppermost barrier layer 142 is non-doped.
[0041] In the first embodiment, the hole blocking layer 13 is provided directly below the active layer 14, so that the entire band of the active layer 14 can be flattened. Therefore, when the active layer 14 is an MQW, the efficiency of hole injection into the well layer 141 on the n-type layer 11 side can be improved. Therefore, the number of well layers 141 in the MQW can be increased more than in the past. For example, while the number of well layers 141 was 1 to 3 in the past, the number of well layers 141 can be 3 to 5 in the first embodiment.
[0042] The electron blocking layer 15 is located on the active layer 14. The electron blocking layer 15 has a two-layer structure in which a first electron blocking layer and a second electron blocking layer are laminated in this order from the active layer 14 side. The electron blocking layer 15 prevents electrons injected from the n-side electrode 18 from diffusing beyond the active layer 14 toward the composition gradient layer 16 side.
[0043] The electron blocking layer 15 does not necessarily have to have a two-layer structure, and may consist of only the first electron blocking layer.
[0044] The first electron blocking layer is made of AlGaN or AlN having a higher Al composition ratio than the barrier layer of the active layer 14, and the Al composition is, for example, 90 to 100%. The first electron blocking layer may be doped with a p-type impurity or may be undoped. The p-type impurity is, for example, Mg. When doped with Mg, the Mg concentration is, for example, 3×10 20 cm -3 The thickness of the first electron blocking layer is, for example, 1 to 10 nm.
[0045] The second electron blocking layer is made of AlGaN having a lower Al composition than the first electron blocking layer, and the Al composition is, for example, 80 to 99%. By providing the second electron blocking layer, the difference in Al composition with the composition gradient layer 16 is adjusted. If the first electron blocking layer is made of AlN alone, the resistance will be high, and if the first electron blocking layer is made thin, the electron blocking performance will decrease. Therefore, by providing the second electron blocking layer, both low resistance and electron blocking function are achieved. The second electron blocking layer may be doped with p-type impurities or may be undoped. In the case of Mg doping, the Mg concentration is, for example, 3×10 20 cm -3 The second electron blocking layer has a thickness of, for example, 1 to 10 nm.
[0046] The compositionally graded layer 16 is located on the electron blocking layer 15. The compositionally graded layer 16 has a two-layer structure in which a first compositionally graded layer and a second compositionally graded layer are laminated in this order from the electron blocking layer 15 side.
[0047] The compositionally graded layer 16 is a layer that has been made p-type by a method called polarization doping. That is, the compositionally graded layer 16 is a layer in which the Al composition changes in the thickness direction, and is set so that the Al composition decreases with increasing distance from the electron blocking layer 15. It was difficult to increase the hole concentration of AlGaN with a high Al composition by Mg doping, but polarization doping can improve the hole concentration and increase the efficiency of hole injection into the active layer 14. In addition, polarization doping does not require Mg doping, so crystallinity can be improved.
[0048] When the Al composition of the compositionally graded layer 16 is set as described above, polarization due to crystal distortion occurs continuously in the compositionally graded layer 16 in the thickness direction. Holes are generated in the compositionally graded layer 16 to cancel the fixed charges caused by this polarization. The generated holes are distributed in the compositionally graded layer 16. Therefore, the holes are widely distributed in the thickness direction from the electron block layer 15 side in the compositionally graded layer 16, and the layer as a whole becomes p-type. In this p-type region, the hole concentration is 1×10 16 ~1×10 20 cm -3 The hole concentration decreases with increasing distance from the electron blocking layer 15. The reason why the number of holes decreases near the interface of the compositionally graded layer 16 with the p-type contact layer 17 is that the Fermi levels attempt to match due to the p-type heterojunction, causing the band to bend.
[0049] The first composition gradient layer is undoped. However, it may be doped with Mg. This is expected to further increase the hole concentration by the p-type impurity. In this case, the Mg concentration is, for example, 1×10 20 cm -3 The following applies.
[0050] The second compositional gradient layer is a layer having a higher Mg concentration than the first compositional gradient layer, and the other portions have the same Al composition as the first compositional gradient layer. That is, the Al composition changes in the thickness direction, and the Al composition is set to decrease with increasing distance from the electron block layer 15. Doping the second compositional gradient layer with Mg enables good connection to the p-type contact layer 17.
[0051] In the first embodiment, the Al composition of the compositionally graded layer 16 decreases continuously, but it may decrease stepwise. However, it is preferable that the region where the Al composition is constant is as small as possible.
[0052] The composition gradient layer 16 does not necessarily have to have a two-layer structure of a first composition gradient layer and a second composition gradient layer, but may have only the first composition gradient layer. Also, it may have a structure of three or more layers with different Al composition change rates, Mg concentrations, etc.
[0053] Instead of the compositionally graded layer 16, a layer made of Mg-doped p-type AlGaN may be provided. In this case, the Mg concentration is, for example, 1×10 17 ~1×10 20 cm -3 The Al composition is, for example, 40 to 80%.
[0054] The p-type contact layer 17 is located on the compositionally graded layer 16. The p-type contact layer 17 is made of Mg-doped p-AlGaN. The Al composition may be smaller than the minimum Al composition of the compositionally graded layer 16, and the Al composition is, for example, 60% or less. The p-type contact layer 17 may be p-GaN. The Mg concentration of the p-type contact layer 17 is, for example, 1×10 20 ~1×10 22 cm -3 The p-type contact layer 17 has a thickness of, for example, 1 to 200 nm.
[0055] The p-type contact layer 17 may be composed of multiple layers with different Al compositions or Mg concentrations. When composed of multiple layers, the top layer in contact with the p-side electrode 19 is preferably p-GaN or AlGaN with a low Al composition. This is to reduce the contact resistance of the p-side electrode 19. In this case, the AlGaN with a low Al composition has an Al composition of 50% or less.
[0056] A groove is provided in a partial area of the surface of the p-type contact layer 17, the depth of which reaches the n-type layer 11. This groove is for exposing the n-type layer 11 so that an n-side electrode 18 can be provided therein.
[0057] The n-side electrode 18 is provided on the n-type layer 11 exposed at the bottom of the groove. The material of the n-side electrode 18 is Ti / Al, V / Al, etc. Here, A / B means that A and B are laminated in order from the n-type layer 11 side.
[0058] The p-side electrode 19 is provided on the p-type contact layer 17. The p-side electrode 19 is a reflective electrode that reflects ultraviolet light emitted from the active layer 14 toward the substrate 10 to increase light extraction efficiency. The material of the p-side electrode 19 is Ru, Rh, Ni / Au, Ni / Al, ITO / Al, or the like. Here, A / B means that A and B are stacked in order from the p-type contact layer 17 side. The p-side electrode 19 may also be a combination of a transparent electrode such as ITO or IZO and a DBR (dielectric multilayer film).
[0059] As described above, in the light-emitting device 1 of the first embodiment, the barrier layer 140 of the active layer 14 has a laminated structure of the undoped first barrier layer 140A and the Si-doped second barrier layer 140B. Since the second barrier layer is doped with Si, the band of the active layer 14 can be flattened to improve the radiative recombination probability. Furthermore, since the undoped first barrier layer 140A is provided, the Si concentration can be reduced in the barrier layer 140 as a whole, and deterioration of characteristics under reverse bias can be reduced.
[0060] Next, various experimental results relating to the first embodiment will be described.
[0061] Experiment 1 In the light-emitting device 1 of the embodiment 1, the hole blocking layer 13 and the active layer 14 were configured as follows (hereinafter, referred to as Example 1). The band diagram and carrier concentration of the light-emitting device of Example 1 were calculated by simulation.
[0062] The layer configuration of the hole blocking layer 13 and the active layer 14 of the light-emitting device 1 of Example 1 is as follows, in order from the substrate 10 side: Hole blocking layer 13 Non-doped AlN Thickness 0.5 nm First barrier layer 140A Non-doped AlGaN (Al composition 68%) Thickness 8 nm Second barrier layer 140B Si-doped AlGaN (Al composition 68%, Si concentration 3×10 18 cm -3 ) Thickness 3nm Well layer 141 Non-doped AlGaN (Al composition 46%) Thickness 2 nm Top barrier layer 142 Non-doped AlGaN (Al composition 68%) Thickness 2 nm
[0063] As a comparative example, the hole blocking layer 13 was omitted from the light emitting device of Example 1, and the two-layer structure of the first barrier layer 140A and the second barrier layer 140B was replaced with a Si-doped AlGaN (Al composition 68%, Si concentration 3×10 18 cm -3 ) and a light-emitting device in which the layer was replaced with a single layer having a thickness of 11 nm (hereinafter, referred to as a light-emitting device of the comparative example), the band diagram and the carrier concentration were calculated in the same manner.
[0064] Fig. 3 shows the case where a voltage of 6 V is applied to the light-emitting element 1 of Example 1, and Fig. 4 shows the case where a voltage of 6 V is applied to the light-emitting element of the comparative example. In Figs. 3 and 4, thin lines indicate band diagrams, and thick lines indicate hole concentrations.
[0065] 4, in the comparative example, the band of the barrier layer 140 has an upward slope to the right. This makes it difficult for holes to move to the n-side. In addition, hole confinement in the well layer 141 is poor.
[0066] On the other hand, as shown in Fig. 3, in the case of the light-emitting device 1 of Example 1, it is found that the band of the barrier layer 140 is flattened compared to that in Fig. 4. It is also found that the amount of holes injected into the well layer 141 is increased. From this, it is considered that the flattening of the band makes it easier for holes to move to the n-side, and the amount of holes injected into the well layer 141 is increased.
[0067] Experiment 2 In the light-emitting device of Example 1, the active layer 14 was changed from SQW to MQW (hereinafter referred to as a light-emitting device of Example 2). Then, the band diagram and carrier concentration of the light-emitting device of Example 2 were calculated by simulation.
[0068] The layer configuration of the hole blocking layer 13 and the active layer 14 of the light emitting device 1 of Example 2 is as follows, from the substrate 10 side: the active layer 14 has two MQW well layers 141. Hole blocking layer 13 Non-doped AlN Thickness 0.5 nm First barrier layer 140A Non-doped AlGaN (Al composition 68%) Thickness 8 nm Second barrier layer 140B Si-doped AlGaN (Al composition 68%, Si concentration 3×10 18 cm -3 ) Thickness 3nm Well layer 141 Non-doped AlGaN (Al composition 46%) Thickness 2 nm First barrier layer 140A Non-doped AlGaN (Al composition 68%) Thickness 8 nm Second barrier layer 140B Si-doped AlGaN (Al composition 68%, Si concentration 3×10 18 cm -3 ) Thickness 3nm Well layer 141 Non-doped AlGaN (Al composition 46%) Thickness 2 nm Top barrier layer 142 Non-doped AlGaN (Al composition 68%) Thickness 2 nm
[0069] As shown in Fig. 5, in the case of the light-emitting device 1 of Example 2, it is seen that the band of the barrier layer 140 is flatter than that in Fig. 4. It is also seen that the amount of holes injected into the well layer 141 is increased. In particular, it is seen that holes are efficiently injected into the well layer 141 on the hole blocking layer 13 side of the two well layers 141. [Explanation of symbols]
[0070] 1: Light emitting element 10: Substrate 11:n-type layer 12: Superlattice layer 13: Hole block layer 14:Active layer 15: Electronic block layer 16: Composition gradient layer 17: p-type contact layer 18:n side electrode 19:p side electrode 140: Barrier layer 141: Well layer 142: Top barrier layer
Claims
1. In an ultraviolet light emitting device using a group III nitride semiconductor, an n-type layer made of an n-type Al-containing Group III nitride semiconductor; an active layer located on the n-type layer, the active layer being made of a group III nitride semiconductor containing Al and having a quantum well structure including a well layer and a barrier layer; a p-type layer located on the active layer and made of a Group III nitride semiconductor containing p-type Al; having The barrier layer comprises: a first barrier layer which is undoped or doped with an n-type impurity; a second barrier layer located on the first barrier layer, in contact with a surface of the well layer facing the n-type layer, and doped with an n-type impurity to a higher concentration than the first barrier layer.
2. 2 . The light-emitting device according to claim 1 , wherein an uppermost barrier layer which is a layer of said barrier layers closest to said p-type layer side is made of a non-doped Group III nitride semiconductor.
3. The first barrier layer is non-doped, and the second barrier layer has a Si concentration of 1×10 18 ~2×10 19 cm -3 The light-emitting device according to claim 1 or 2, wherein
4. 3. The light-emitting device according to claim 1, wherein the first barrier layer has a thickness of 2 to 20 nm, and the second barrier layer has a thickness of 2 to 20 nm.
5. 3. The light-emitting device according to claim 1, further comprising a hole blocking layer made of AlGaN or AlN having a higher Al composition than said barrier layer, said hole blocking layer being located between said n-type layer and said active layer in contact with said active layer.
6. 6. The light-emitting device according to claim 5, further comprising a superlattice layer located between said n-type layer and said hole blocking layer in contact with said hole blocking layer, said superlattice layer being formed by alternately stacking Group III nitride semiconductors having different Al compositions.
7. The light-emitting device according to claim 5 , wherein the active layer has an MQW structure.
Citation Information
Patent Citations
Light emitting diode having active region of multiquantum well structure
JP2013118412A
Distortion-balancing laser diode
JP2014506017A
Nitride semiconductor light-emitting device
JP2023008449A
Semiconductor Device Structures with Modulated Doping and Related Methods
US20110140083A1
Deep ultraviolet LED in which quantum barrier was doped and manufacturing method
JP2021034732A